2016
DOI: 10.1002/mnfr.201600549
|View full text |Cite
|
Sign up to set email alerts
|

An extra virgin olive oil rich diet intervention ameliorates the nonalcoholic steatohepatitis induced by a high‐fat “Western‐type” diet in mice

Abstract: Dietary EVOO could repair HFD-induced hepatic damage, possibly via an anti-inflammatory effect in adipose tissue and modifications in the liver lipid composition and signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 38 publications
5
42
1
Order By: Relevance
“…Interestingly, at 24 h postinjection, most of the E‐MPNs were eliminated from the spleen, liver, and lungs, with only about 1%, 10%, and 0.5% remaining, respectively, indicating that the particles are biodegradable in these organs over time. This property is likely related to the stability of the MPN coating with pH and the metabolism of fatty acids in the liver (i.e., OA) . All animals survived the study—mice were active and showed no signs of lethargy or ill health after being dosed with known quantities of E‐MPNs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, at 24 h postinjection, most of the E‐MPNs were eliminated from the spleen, liver, and lungs, with only about 1%, 10%, and 0.5% remaining, respectively, indicating that the particles are biodegradable in these organs over time. This property is likely related to the stability of the MPN coating with pH and the metabolism of fatty acids in the liver (i.e., OA) . All animals survived the study—mice were active and showed no signs of lethargy or ill health after being dosed with known quantities of E‐MPNs.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acid analysis and determination of total phenols was assessed as previously described . The olive oil used in the HFD‐EVOO group presented a 79.58% of oleic acid respect to total fatty acid content and 79 mg kg –1 of total phenolic compounds expressed as tyrosol equivalents, and the olive oil used in the HFD‐OL group, a 77.66% of oleic acid and 444 mg kg –1 of total phenolic compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have shown that oils high in MUFAs or PUFAs have attenuated the effects of dietaryinduced NAFLD. Mice that were fed an HF diet (49% energy from fat) for 12 wk and fed phenol-rich extra virgin olive oil (41.7% energy from olive oil) had an improved lipid profile, decreased visceral adipocyte inflammatory cytokine expression, and improved NASs compared with mice fed an HF diet without extra virgin olive oil (83). The mean NAS of mice fed the HF diet was >4, whereas mice fed the extra virgin olive oil and phenol-rich extra virgin olive oil had NASs of 3 and 2, respectively (83).…”
mentioning
confidence: 99%
“…Mice that were fed an HF diet (49% energy from fat) for 12 wk and fed phenol-rich extra virgin olive oil (41.7% energy from olive oil) had an improved lipid profile, decreased visceral adipocyte inflammatory cytokine expression, and improved NASs compared with mice fed an HF diet without extra virgin olive oil (83). The mean NAS of mice fed the HF diet was >4, whereas mice fed the extra virgin olive oil and phenol-rich extra virgin olive oil had NASs of 3 and 2, respectively (83). In addition, menhaden oil, which is rich in PUFAs such as EPA (20:5n-3) and DHA (22:6n-3), has been shown to improve the hepatic damage induced by a high-fat, high-cholesterol (HFHCH) diet in both wildtype mice and genetic animal models of hyperlidemia (84).…”
mentioning
confidence: 99%